Mentalities and Slavery in the Colonial Atlantic World: Didactic Strategy to Fight Against Anachronism - Menjívar Ochoa, Mauricio (2016)
This article shows a didactic strategy for the unit of the course of History of Culture at the Escuela de Estudios Generales in the Universidad de Costa Rica. This strategy corresponds to one of the units whose objective is to characterize the slavery at the Colonial Atlantic World. The purpose of this unit is to appreciate the implications of slavery in those human beings. First, this article shows the difficulty of understanding the mentality of the social subjects from the past because it seems an anachronism. Second, this strategy, inspired in methodology of inter-learning, is explained. Finally, this article exposes the evaluation of the different components of the strategy made by the students of the course. Although it is difficult for the students to stand in the shoes of the slavery people, the strategy help not only to acquire the knowledge in a dynamic way, but also to develop sensibility with the situation. The most relevant conclusions are the ludic character of the strategy and its relevance in the teaching-learning process.